Problems of Information Support of Political Management in the Knowledge Society - Yury Vasilyevich Kosov; Igor Mikhailovich Levkin (Управленческое консультирование, 2018)
In the article the main problems of information support of political management at the new stage of society development - knowledge society. It is noted that in these conditions dramatically increases the amount of information is reduced structuring, increases the dynamics of the updates. It is shown that the performance of the basic requirements for information assurance: completeness, accuracy, targeting, and efficiency of providing the information will require a revision of views on the structure of a single information space, principles and procedure of application state information structures and specialized centers.